(3TQM LeY GdLhGeY aj CUhd Gdabgs - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi CaVGdg hGdSdGe Ydi SjOfG eMeO hBdg gPG eG ETJOJ Edjg MGLI GdeJagejf , GdLeY GdLhGeY , ef TQM jMd CdaGXg , hjHjf eQGOg s
(3BNQgG (B:s
(3Gddge jG PG GdaVd GdYXje , JaVd YdjfG HGdYah hHeG JTGA ef GdfYje hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HChdg JedjcGJ HYO GdCda GdgLQi Ydi MhGTjgG JYdjbGJs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
Keywords: (3Gdabg GdESdGejs